(untitled) (Jurnal Lemhannas RI, 2025)
Purpose: This study analyses the role of sustainable agricultural innovation in strengthening food self-sufficiency as a foundation for national resilience in responding to climate change, geopolitical dynamics, and import dependence. Study Design/Methodology/Approach: The study applies a qualitative descriptive approach combined with policy analysis and a SWOT framework to examine institutional capacity, governance, and innovation pathways through the evaluation of national policies, regulations, and strategic agricultural programmes. The analysis integrates content analysis, SWOT assessment, and data triangulation to ensure consistency of findings, while the Asta Gatra framework is used to examine the multidimensional relationship between agricultural innovation, food self-sufficiency, and national resilience. Findings: The results indicate that sustainable agricultural innovation improves production efficiency through the implementation of smart agriculture, mechanisation, and climate-adaptive practices. However, the impact remains uneven due to low levels of technology adoption, limited human resource capacity, and weak institutional coordination. These structural constraints influence the stability of food production, distribution, and access, particularly under external pressures related to climate change, global price volatility, and dependence on imports. Originality/Value: The study positions sustainable agricultural innovation as an integrated system linking technology, human capacity, and governance within the Asta Gatra framework. The analysis provides conceptual and policy contributions to strengthening food self-sufficiency and national resilience under conditions of global uncertainty.